Predicting gas dispersion in large scale underground ventilation: A particle tracking approach. (January 2016) - Widiatmojo, Arif; Sasaki, Kyuro; Widodo, Nuhindro Priagung; Sugai, Yuichi; Sahzabi, Amin Yousefi; Nguele, Ronald
Abstract: The present work highlights the gas dispersion evaluation in large underground tunnel ventilation by means of tracer gas measurement and numerical simulation using particle tracking method. Ventilation system is a tool to control pollutants and/or hazardous gas spreading. The use of grid-based numerical method is limited by the spatial dimension of ventilation network. Therefore, the applicability of such technique for large ventilation network is constrained. A Lagrangian based Particle Tracking method is proposed to evaluate the dispersion of tracer gas from a releasing point to the downstream position in a complex ventilation system. This method simulates mass transport by discretizing mass concentration into numbers of particles. Rather to solving the transport equation in grid system to obtain the mass concentration, this technique simulates mass concentration by counting number of particles at any specified position within the ventilation network. In this research, the network splitting scheme was used to simulate particles' transition in junctions. Further, it was found that by setting effective diffusion coefficient to 47 times larger than those for common underground airway and with velocity correction factor of α = 0.59, a good agreement between particle tracking result and tracer gas measurement data can be achieved. This results suggests that the analytical approach in evaluating gas (or pollutant) dispersion and residence time in large ventilation system by the means of conventional ventilation network analysis have to consider both mechanical dispersion and the effect of delay due to trapping mechanism of gas. Highlights: Particle tracking method was used to simulate gas dispersion. Tracer gas measurement in underground mine was simulated. Effective diffusion coefficient was 47 times higher than for normal airway. Average velocity was 0.59 times slower than the actual measurement. Gas residence time was 2.25 times longer than if normal airways were considered.